Problems of limited-data wave tomography - Goncharsky, A.V.; Romanov, S.Yu.; Seryozhnikov, S.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
A number of schemes of full-range and limited-data wave tomography are compared. Inverse problems of tomography are treated as coefficient inverse problems for the wave equation. The proposed algorithms for solving inverse problems are based on direct computation of the residual functional by solving the conjugate problem for the hyperbolic partial differential equation. Reflection and transmission tomography schemes are analyzed. Numerical simulations are performed both in the two- and three-dimensional versions on the GPU cluster of Lomonosov supercomputing facility of Moscow State University.